Making Qualified Visum et Repertum of Living Victims in Lubuk Pakam Hospital, Kabupaten Deli Serdang - Petrus, Asan; Parinduri, Abdul Gafar; Lubis, Adriansyah (Talenta Publisher, 2022)
Visum et repertum is one of the legal evidence in court that plays a role in the process of proving a case, so that the crime that occurs becomes clearer, the visum et repertum is made based on the results of the doctor's examination and must be of good quality. Thus, the function and role of the visum et repertum is fulfilled, but based on the research we conducted in July 2019 on the visum et repertum issued by Lubuk Pakam Hospital from January 1, 2017 to December 31, 2018 the quality was not good enough. Efforts to realize a good quality visum et repertum in our opinion needed technical guidance in the form of lectures and questions and answers as well as training/workshops on making good visum et repertum. Potential groups to be trained are general practitioners who work in the Emergency Unit of Lubuk Pakam Hospital, Deli Serdang Regency, who are trained to increase their knowledge and skills in making good quality visum et repertum. The method of carrying out activities is the lecture and question and answer method which is then followed by a workshop on good visum et repertum making techniques with a period of every 2 months as many as 3 times for 6 months, then several visum evaluations will be carried out to see the progress of the quality of the visum et repertum issued by Lubuk Pakam Hospital after training.